A visit to preanesthesia clinic can promote post-anesthesia early recovery in pediatric patients undergoing minor surgery: a retrospective study from a single center - Huanqi Luo; Dongdong Zhang; Yujun Lian; Yunfei Yan; Ting Zhang; Yanyan Sun (BMC Anesthesiology)
Abstract Background The preanesthesia clinic has been established for decades, with numerous studies confirming its advantages. However, in certain countries or regions, preanesthesia clinic services have yet to be implemented or have encountered resistance during their development. Moreover, there is little literature addressing whether preanesthesia clinic benefits healthy patients undergoing minor surgical procedures. Therefore, this study was conducted to explore whether the preanesthesia assessment model influences short-term post-anesthesia recovery, aiming to uncover additional benefits of preanesthesia clinic. Methods Pediatric patients aged 1 to 18 years underwent elective adenoidectomy or adenotonsillectomy under general anesthesia were included, who were divided into the two groups according to different models of preoperative anesthesia evaluation. The primary outcomes were the extubation time and the length of postanesthetic care unit stay. The secondary outcomes were the length of hospital stay, the medical costs, and postoperative complications. Results Total 1553 eligible pediatric patients were enrolled, 492 finished preoperative evaluation in preanesthesia clinic, another 1061 in wards. Compared with the model of preoperative anesthesia evaluation in ward, the length of postanesthetic care unit stay, the examination costs, the costs of laboratory test, and the total medical costs were significantly lower in the preanesthesia clinic group. Conclusions Preanesthesia clinic can significantly shorten the post-anesthesia recovery time for healthy children undergoing minor surgeries and can reduce overall medical costs. Trial registration The study was retrospectively registered at Chictr.org.cn with the number ChiCTR2300070212 on 04/05/2023.